On how Virginia Woolf Disrupts the Victorian Ideal of ‘the Angel in the House’ in her Fictional and Critical Writings - Betsabé Asprón Amaya, Dámaris (Journal of Artistic Creation and Literary Research, 2025)
This paper explores the process of disruption of the Victorian model of ‘the Angel in the House’ in two works by Virginia Woolf: The Voyage Out and Three Guineas. The analysis of the character of Rachel in The Voyage Out has enabled us to look at the rules and norms that society set for women in their struggle to find their own role and identity in society. Three Guineas provides us with Woolf’s arguments against the patriarchal state that have set women as outsiders. Although there is a gap of 23 years in the publication of both works, it is interesting to look at the themes and issues that arise in Woolf’s first novel and how she still sees these issues as crucial well after two decades and in the interwar period in the 20th-century. For this reason, it could be argued that Woolf’s representation of the consequences of patriarchal values in The Voyage Out is less explicit than in Three Guineas, where the call for an end of these values is much clearer than in her first novel.